On the HK Completions of Sequence Spaces - Abduallah Hakawati; K. Snyder (My University, 1994)
If the space ? (the finite sequences) is equipped with the norm which is naturally induced by a positive definite Hermitian and diagonally blockwise constructed matrix, then an HK completion exists.